2020
DOI: 10.1111/hiv.13007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and incidence of pre‐diabetes and diabetes mellitus among people living with HIV in Ghana: Evidence from the EVERLAST Study

Abstract: Background Available data from high‐income countries suggest that people living with HIV (PLWH) have a four‐fold higher risk of diabetes compared with HIV‐negative people. In sub‐Saharan Africa, with 80% of the global burden of HIV, there is a relative paucity of data on the burden and determinants of prevalent and incident dysglycaemia. Objectives To assess the prevalence and incidence of pre‐diabetes (pre‐DM) and overt diabetes mellitus (DM) among PLWH in a Ghanaian tertiary medical centre. Methods We first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 59 publications
1
13
2
Order By: Relevance
“…Our study showed overall prevalence of T2DM in 187 WLWH who received ARTs as 22 (11.8%), using FPG, 2hrs Postprandial OGTT glucose and HbA1c which was higher than the report by [18] in 2020 from Ghana who reported a prevalence of 7.4% [19]. The disagreement may be as a result of differences in age of study population.…”
Section: Resultscontrasting
confidence: 58%
“…Our study showed overall prevalence of T2DM in 187 WLWH who received ARTs as 22 (11.8%), using FPG, 2hrs Postprandial OGTT glucose and HbA1c which was higher than the report by [18] in 2020 from Ghana who reported a prevalence of 7.4% [19]. The disagreement may be as a result of differences in age of study population.…”
Section: Resultscontrasting
confidence: 58%
“…The need for a greater focus towards prevention and early detection of CKD in low-and middle-income countries has been emphasized in global health literature 47,48 , in part because treatment for ESRD is highly specialized 49 and costly for healthcare systems already challenged with scarcer resources than HICs. This is particularly important since other comorbidities contributing to CKD are increasingly seen in this population 50,51 .…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic disorders such as diabetes mellitus (DM) have been associated with HIV and ARVs ( Echecopar-Sabogal et al, 2018 ; Sarfo et al, 2021 ), and carbohydrate metabolism abnormalities like insulin resistance, hyperglycemia, and DM have been associated with ARVs of the class protease inhibitors (PIs) ( Noor et al, 2006 ). Some earlier PIs such as indinavir and lopinavir/ritonavir exasperate lipid profiles and increase the risk of developing insulin resistance, hyperglycemia, and DM ( Overton et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%